Function and regulation mechanism of Chk1 during meiotic maturation in porcine oocytes. Issue 22 (17th November 2017) - Nie, Zheng-Wen; Chen, Li; Jin, Qiu-Shi; Gao, Ying-Ying; Wang, Tao; Zhang, Xia; Miao, Yi-Liang
ABSTRACT: Checkpoint 1 (Chk1), as an important member of DNA replication checkpoint and DNA damage response, has an important role during the G2/M stage of mitosis. In this study, we used porcine oocyte as a model to investigate the function of Chk1 during porcine oocyte maturation. Chk1 was expressed from germinal vesicle (GV) to metaphase II (MII) stages, mainly localized in the cytoplasm at GV stage and moved to the spindle after germinal vesicle breakdown (GVBD). Chk1 depletion not only induced oocytes to be arrested at MI stage with abnormal chromosomes arrangement, but also inhibited the degradation of Cyclin B1 and decreased the expression of Mitotic Arrest Deficient 2-Like 1 (Mad2L1), one of spindle assembly checkpoint (SAC) proteins, and cadherin 1 (Cdh1), one of coactivation for anaphase-promoting complex/cyclosome (APC/C). Moreover, Chk1 overexpression delayed GVBD. These results demonstrated that Chk1 facilitated the timely degradation of Cyclin B1 at anaphase I (AI) and maintained the expression of Mad2L1 and Cdh1, which ensured that all chromosomes were accurately located in a line, and then oocytes passed metaphase I (MI) and AI and exited from the first meiotic division successfully. In addition, we proved that Chk1 had not function on GVBD of porcine oocytes, which suggested that maturation of porcine oocytes did not need the DNA damage checkpoint, which was different from the mouse oocyte maturation.